Fostering critical thinking in learning outcomes of Kazakhstan initial teacher education - Kabysheva, Mariya (Frontiers in Education, 2025)
The integration of critical thinking into initial teacher education programs is crucial to achieving the United Nations' Sustainable Development Goals, particularly SDG 4, as teachers play a pivotal role in fostering this essential competency. This study employs computer algorithms to analyze how Kazakhstani educational program developers incorporate critical thinking into learning outcomes. The data sources include Russian-language versions of all active bachelor's degree teacher education programs in Kazakhstan. A first-in-kind mapping was constructed linking Russian verbs to Bloom's Taxonomy cognitive skill levels for this analysis. The methodological approach utilizing automated verb frequency analysis offers a practical tool not only for initial evaluation but also for ongoing, repeatable assessments of curricula. The findings indicate that while direct mentions of “critical thinking” are present, and some higher-order thinking skill verbs are utilized, critical thinking remains modestly integrated into learning outcomes.